2018
DOI: 10.1039/c8dt02919a
|View full text |Cite
|
Sign up to set email alerts
|

Stable Fe(iii) phenoxyimines as selective and robust CO2/epoxide coupling catalysts

Abstract: Three phenoxyimine Fe(iii)Cl complexes bearing electronically diverse -Cl, -H or -Bu substituents in the ortho position were synthesised. X-ray crystallographic analysis of the complexes reveals mononuclear structures with pentacoordinate iron centres and trigonal bipyramidal geometries. All three complexes demonstrated excellent catalytic activities towards CO/epoxide coupling to selectively form cyclic carbonates, with catalyst activity correlating with the electron withdrawing nature of the ortho-substituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
(63 reference statements)
8
18
0
Order By: Relevance
“…The increase of activity with an increase of flexibility agrees with that observed by Garden and Lamberti. 9,54 The Fe(III)-salan-acetate complexes were generally more effective than the salalen complexes. Modifying the ethylene backbone to bipyrrolidine and changing the hybridisation of the nitrogen atom from imine to amine (salalen to salan) offered minimal improvement in activity.…”
Section: Epoxide and Co 2 Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of activity with an increase of flexibility agrees with that observed by Garden and Lamberti. 9,54 The Fe(III)-salan-acetate complexes were generally more effective than the salalen complexes. Modifying the ethylene backbone to bipyrrolidine and changing the hybridisation of the nitrogen atom from imine to amine (salalen to salan) offered minimal improvement in activity.…”
Section: Epoxide and Co 2 Couplingmentioning
confidence: 99%
“…[5][6][7][8]42,[50][51][52][53] A variety of ligand classes have been applied specifically to iron and recently these were reviewed by Della Monica et al 5 Salen, bidentate phenoxyimine (half salen) and, recently, salalen and salan ligands have all been successfully applied to the selective formation of COCs. [54][55][56][57][58] Lamberti and co-workers reported the first such example of the application of Fe-salan and -salalen complexes, together with Fe-salen complexes for comparison, for the coupling of CO 2 with propylene oxide (PO), cyclohexene oxide (CHO) and styrene oxide (SO). 9 Varying the hybridisation of the nitrogen donor atoms, and maintaining the ethylene backbone, aromatic groups and chloride auxiliary group, it was observed that at 100°C and 20 bar of CO 2 the order of reactivity decreased from salan to salen to salalen.…”
Section: Introductionmentioning
confidence: 99%
“…This valve is moderately high, and exceeds some reported vales. [52][53][54][55][56] In contrast, the individual catalytic efficiency of 1-Eu or TBAB for PO was very low (Table 1, entries 1and 2).…”
Section: Catalytic Propertymentioning
confidence: 99%
“…Later, Garden et al. investigated the catalytic behaviour of a new group of phenoxy‐iminic complexes (Figure ) . Using the formation of PC as benchmark, with 0.05 mol% of Fe, 0.1 mol % of TBAB, at 120 °C and 20 bar of CO 2 , the authors found that the ortho ‐substituents influence the catalytic activity, observing the trend 15c > 15a > 15b .…”
Section: Phenoxy‐based Ligandsmentioning
confidence: 99%